2019
DOI: 10.3390/molecules24183384
|View full text |Cite
|
Sign up to set email alerts
|

Accramycin A, A New Aromatic Polyketide, from the Soil Bacterium, Streptomyces sp. MA37

Abstract: Drug-like molecules are known to contain many different building blocks with great potential as pharmacophores for drug discovery. The continued search for unique scaffolds in our laboratory led to the isolation of a novel Ghanaian soil bacterium, Streptomyces sp. MA37. This strain produces many bioactive molecules, most of which belong to carbazoles, pyrrolizidines, and fluorinated metabolites. Further probing of the metabolites of MA37 has led to the discovery of a new naphthacene-type aromatic natural produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(69 citation statements)
references
References 42 publications
3
66
0
Order By: Relevance
“…Gentamicin (Sigma) was used as the standard antibiotic. The antibacterial assay of 1 was performed as described in our previous report [26].…”
Section: Chromatography and Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Gentamicin (Sigma) was used as the standard antibiotic. The antibacterial assay of 1 was performed as described in our previous report [26].…”
Section: Chromatography and Isolationmentioning
confidence: 99%
“…MA37. This strain is a prolific producer of natural products including legonmycins [21], neocarazostatin A [22][23][24][25], accramycin A [26], legonoxamines [27], and organofluorines [9,28]. However, genomic analysis of the MA37 strain suggested that only a small part of the biosynthetic genes encoding for specialised metabolites were expressed under laboratory culture conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In our efforts to discover natural products, we have isolated a new bacterial strain, Streptomyces sp. RK44 from the underexplored areas of Kintampo waterfalls, Ghana, Africa [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…MA37 is a highly prolific producer of SMs with great chemical diversity, including pyrrolizidine alkaloids [11], carbazoles [12][13][14][15][16], siderophores [17,18], and fluorinated compounds [19][20][21][22][23][24]. More recently, we discovered a new naphthacemycin congener, accramycin A 1, as one of the minor SMs in the MA37 wild type (WT) strain (0.2 mg/L) [25]. Two mono-chlorinated accramycin derivatives were also tentatively assigned via molecular network analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the previous knowledge of fasamycins and formicamycins [4], the putative biosynthetic gene cluster (acc BGC) of 1 was identified [25]. The biosynthetic enzymes encoded in the acc BGC displays high amino acid (AA) similarity with the ones in fasamycins and formicamycins, including the FADdependent halogenation enzyme (AccV) which shares high AA identity to the chlorinase, ForV encoded in the fasamycin and formicamycin BGCs from Streptomyces formicae [4].…”
Section: Introductionmentioning
confidence: 99%